2021
DOI: 10.1039/d1tc03205d
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of metal-ion co-doping towards boosting upconversion luminescence in gadolinium vanadate

Abstract: Effect of (a) particle size, (b) lattice shrinkage, and (c) vacancies on the upconversion luminescence in GdVO4:Yb3+/Er3+. The colored spheres represent the different systems (left) with the respective volumes being proportional to the quantum yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…As a result, using Zn 2+ as a substitutional dopant at Gd 3+ sites reduce the cell volume significantly, improving optical performance. 47,101…”
Section: Enhancing Upconversion Intensity and Tunable Emission Throug...mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, using Zn 2+ as a substitutional dopant at Gd 3+ sites reduce the cell volume significantly, improving optical performance. 47,101…”
Section: Enhancing Upconversion Intensity and Tunable Emission Throug...mentioning
confidence: 99%
“…In oxide and fluoride host lattices with lanthanide activators, successful examples of boosting upconversion emission have been reported with co-doping TM n+ for the following ions: Mn 2+ , Cu 2+ , Co 2+ , Ni 2+ , Cr 3+ , Fe 3+ , Zn 2+ , Cd 2+ , and Mo 3+ . [42][43][44][45][46][47][48][49] UC luminescence can be tuned by controlling the doping concentration of the transition metal ions. For instance, Wei et al 50 reported that the strongest UC emission intensity was obtained in Fe 3+ co-doped NaGdF 4 :20 mol%Yb 3+ ,2 mol%Er 3+ , when the stoichiometric ratio of Fe 3+ was 20 mol%.…”
Section: Transition Metal Ion Co-dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Particularly, host lattice modulation by the doping of inactive ions has oen been used to alter the f-f transition probability, which helps in improving the UC intensity. 13,14 These ions may occupy the substitutional or interstitial sites in the crystal lattice and modify the crystal symmetry around the RE ions. The aer-effects are interpreted in terms of induced lattice strain, a change in the crystallite size, phase transformations, and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the methods to improve the luminescence intensity of up-conversion materials and enhance the upconversion imaging effect include ion doping, chemical modification and physical regulation. Chauhan et al doped GdVO4:Yb 3+ , Er 3+ up-conversion materials by Sc 3+ and Zn 2+ , and the up-conversion luminescence intensity increased by 50 times compared with undoped materials [7]. Although the conversion luminescence intensity of up-conversion materials is significantly improved by ion doping, the up-conversion materials prepared in this way are still in the laboratory stage due to unstable properties and complex preparation process.…”
Section: Introductionmentioning
confidence: 99%